Dengeki Daisy. Vol. 12 - Motomi, Kyousuke (Shojo beat manga., 2013)
"Teru and her friends sneak aboard a yacht in order to save Rena and foil Morizono's plan to sell the new 'Jack Frost' virus. The rescue mission turns out to be more than anyone bargained for, however, when Kurosaki runs into a man who makes his blood turn cold"--Publisher's web site.